2010
DOI: 10.1002/art.27300
|View full text |Cite
|
Sign up to set email alerts
|

Antimalarial treatment may have a time‐dependent effect on lupus survival: Data from a multinational Latin American inception cohort

Abstract: Objective. To evaluate the beneficial effect of antimalarial treatment on lupus survival in a large, multiethnic, international longitudinal inception cohort.Methods. Socioeconomic and demographic characteristics, clinical manifestations, classification criteria, laboratory findings, and treatment variables were examined in patients with systemic lupus erythematosus (SLE) from the Grupo Latino Americano de Estudio del Lupus Eritematoso (GLADEL) cohort. The diagnosis of SLE, according to the American College of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
116
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 190 publications
(127 citation statements)
references
References 23 publications
(31 reference statements)
6
116
0
5
Order By: Relevance
“…A similar approach was previously employed by Houssiau et al [16] to evaluate the time to renal flare in the MAINTAIN trial. The same approach has been used in prospective cohort studies to evaluate the risk of SLE organ damage and mortality [17,18]. We found a relatively low proportion of patients suffering flares as compared with other cohort studies [1,5,19].…”
Section: Discussionsupporting
confidence: 50%
“…A similar approach was previously employed by Houssiau et al [16] to evaluate the time to renal flare in the MAINTAIN trial. The same approach has been used in prospective cohort studies to evaluate the risk of SLE organ damage and mortality [17,18]. We found a relatively low proportion of patients suffering flares as compared with other cohort studies [1,5,19].…”
Section: Discussionsupporting
confidence: 50%
“…When we recalculated the median (range) CLASI activity score of all 11 patients, it changed from 6.0 (0-12) to 5.0 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). Response to antimalarials in 36 patients with lupus erythematosus tumidus was reported recently.…”
Section: Discussionmentioning
confidence: 98%
“…In a Spanish cohort it was shown that antimalarials reduced the risk of thrombosis by 72%, that of major infection by 94%, and that of death by 86% [5,6]. In a Latin American cohort it was shown that antimalarials reduced the risk of death, in a time-dependent manner, by 38% [7]. A recent systematic review concluded that, given the broad spectrum of beneficial effects and the safety profile of HCQ, it should be given to most patients with SLE during the whole N. Yokogawa course of the disease, irrespective of its severity, and be continued during pregnancy [8].…”
Section: Introductionmentioning
confidence: 99%
“…HCQ lowers disease activity and inflammation in SLE, and it has been reported that early initiation of HCQ delays the onset and progression of disease and ameliorates overall survival [36][37][38][39][40][41][42].…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%